2021
DOI: 10.1093/gbe/evab245
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial adaptation by a transposition burst of an invading IS element

Abstract: The general importance of transposable elements (TEs) for adaptive evolution remains unclear. This in part reflects a poor understanding of the role of TEs for adaptation in non-model systems. Here, we investigated whether insertion sequence (IS) elements are a major source of beneficial mutations during 400 generations of laboratory evolution of the cyanobacterium Acaryochloris marina strain CCMEE 5410, which has experienced a recent or on-going IS element expansion and has among the highest transposase gene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…For long, transposition of IS was associated to fitness loss due to gene inactivation or expression changes. Here, we provide more evidence that IS can increase fitness and play an important role in adaptation, as was already shown across different species ranging from Enterobacteria (Consuegra et al 2021 , Frazão et al 2022 ) to Cyanobacteria (Miller et al 2021 ). A recent study in Bacillus subtilis and Bacillus thuringensis revived end-point populations from four different evolution experiments and showed that, independently of growth in either biotic or abiotic conditions, insertion sequences are critical in adaptation (Hu et al 2023 ).…”
Section: Discussionsupporting
confidence: 76%
“…For long, transposition of IS was associated to fitness loss due to gene inactivation or expression changes. Here, we provide more evidence that IS can increase fitness and play an important role in adaptation, as was already shown across different species ranging from Enterobacteria (Consuegra et al 2021 , Frazão et al 2022 ) to Cyanobacteria (Miller et al 2021 ). A recent study in Bacillus subtilis and Bacillus thuringensis revived end-point populations from four different evolution experiments and showed that, independently of growth in either biotic or abiotic conditions, insertion sequences are critical in adaptation (Hu et al 2023 ).…”
Section: Discussionsupporting
confidence: 76%
“…strain Awaji, discovered by Murakami, et al [15] in Japan, for which there is no full genome sequence. However, it is closest in full genome comparison to strain S15 from the California coast [65], both epiphytes of red algae in the Pacific. Like strain S15, the Moss Beach strain also lacks complex phycobilisomes, as compared to type strain MBIC11017, perhaps indicating an adaptation to their similar red (or brown for strain Moss Beach) algal epiphyte spectral environment.…”
Section: Discussionmentioning
confidence: 97%
“…Paired end short-read sequencing was performed with MiSeq500 v2 (Illumina). For R. gibba , high molecular weight DNA was also extracted using the protocol described elsewhere [ 23 ], prepped using a MinION Ligation Sequencing Kit, and sequenced using a FLO-MIN106 flow cell (Oxford Nanopore). All library preparations and sequencing were performed at the University of Montana Genomics Core.…”
Section: Methodsmentioning
confidence: 99%